2021
DOI: 10.31234/osf.io/ayve7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Neuroscience and Entrepreneurship: cross-disciplinary review and future potential

Abstract: Research on entrepreneurial cognition and uncertainty has existed for decades, yet most empirical studies have not integrated methods or concepts from neuroscience. To address this, we provide a framework to unpack the micro-foundations of entrepreneurial cognition. Leveraging theories of cognitive control we show how novel actions are produced, and how the resulting uncertainty can be mediated by context, emotions, social cognition, and metacognition. In addition, by summarising where neuroscience methods hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(206 reference statements)
0
1
0
Order By: Relevance
“… Jiatong et al (2021) concluded that cognitive flexibility is not only positively related to entrepreneurial intentions as well as alertness but also has an indirect relation of alertness with cognitive flexibility via entrepreneurial efficacy. Clements et al (2021) provided a framework that helps to understand entrepreneurial cognitions. The framework deals with how novel actions are rendered and how uncertainty is mediated by context, emotion, social cognitions, and metacognition.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“… Jiatong et al (2021) concluded that cognitive flexibility is not only positively related to entrepreneurial intentions as well as alertness but also has an indirect relation of alertness with cognitive flexibility via entrepreneurial efficacy. Clements et al (2021) provided a framework that helps to understand entrepreneurial cognitions. The framework deals with how novel actions are rendered and how uncertainty is mediated by context, emotion, social cognitions, and metacognition.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%